Robbing Woodchester: Narrative Strategies in Bishop Wærferth’s Dispute Memorandum, Sawyer 1441 - Hanlon, Brittany (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Since Simon Keynes’s line-by-line exegesis (1992), the Fonthill Letter (S 1445) has been subject to a range of interdisciplinary approaches, including linguistic, palaeographical, historical, and literary analysis. It is evident that other vernacular documents generated by processes of litigation during the Alfredian period would benefit from a Keynes-style interpretative commentary. This article conducts a close reading of the language employed by Worcester charter draftsmen in the dispute memorandum, also known as Sawyer 1441, that records the dispute settled between Bishop Wærferth of Worcester and the priest Æthelwald concerning the woodland at Woodchester. This study establishes the importance of reading early English charters through the lens of narrative strategy by focusing on two phrases: bereafian, meaning "to rob" or "to seize" and geniman, which can be translated as "to take away" or "to seize." Worcester’s charter draftsmen consciously selected vocabulary that would protect their leased properties and positioned Worcester as victim to greedy rival claimants. By exploring the meaning and function of these phrases in contemporary Alfredian literature and earlier Latin diplomas, this study demonstrates that Alfredian charters were not written in abstract and interacted with what would now be considered as literary contexts.